LESSON STUDY: PENINGKATAN KOMPETENSI PEDAGOGIK MAHASISWA PRAKTIK PENGALAMAN LAPANGAN (PPL) DI SMP KOTA TARAKAN - Arifin Arifin; Uli Agustina Gultom (Universitas Negeri Makassar, 2016)
The study was conducted with the purpose to describe the students’ motivation in practicing Lesson Study at Teaching Practice Program (PPL) for increasing their pedagogic competence. There were five teacher trainees who joined in Teaching Practice Program and they were as teacher models in Lesson Study at SMP Negeri 3, 5 and 7 in Tarakan. Research design of this research was describtive qualititave with snowballing technique data analysis started on April to October, 2016. Lesson Study consists of three steps; Plan, Do and See. The result of the research can be revealed that 1) students, as teacher trainees, are able to improve their teachng quality through practicing Lesson Study at SMP by having good lesson plan, teaching preparation, classroom management, teaching instructional material, good interaction between teacher and students, 2) the Lesson Study also has significant role in empowering English language teacher trainees to generate the students’ performance at the classroom interaction by sharing idea from all teacher trainees in teaching reflection session.